A Growth Initiation Factor for Host-Independent Derivatives of Bdellovibrio bacteriovorus - Ishiguro, Edward E. (1973)
Host-independent (H-I) derivatives of Bdellovibrio bacteriovorus 109 Davis could not be isolated when concentrated suspensions of host-dependent (H-D) cultures, washed free of spent medium, were plated on host-free media. However, H-I colonies did appear when spent broth was incorporated into the isolation medium, indicating the presence of a factor in the spent medium essential for the growth of H-I cells. This growth factor (GIF) was also present in cell-free extracts of Escherichia coli and a variety of other microorganisms including H-D and H-I derivatives of strain 109 Davis. GIF was heat stable, non-dialyzable, and present in both soluble and particulate fractions of extracts. Heating of extracts at 70 C for 10 min resulted in 10- to 40-fold stimulation in GIF activity, and evidence for a heat-labile inhibitor was obtained. Colonies appearing on host-free medium in these experiments were shown to be those of typical H-I derivatives by isolation and subsequent host-independent cultivation of these organisms. GIF was a conditional requirement dependent on age and size of inoculum for all H-I derivatives characterized. Although GIF stimulated the growth of washed exponential phase cells transferred to fresh medium, it was not essential for growth. However, it was essential for the initiation of growth of washed stationary phase cells from small inocula transferred to fresh medium. It is proposed that GIF is required to initiate growth of metabolically quiescent cells.